Diagnosis of intestinal ischemia by measurement of serum phosphate and enzyme changes and the effectiveness of vitamin E treatment - Hakan UNCU; Gürkan UNCU; Yeşim İLÇÖL and Yalçın AKER (Turkish Journal of Gastroenterology, 2019)
-